2021
DOI: 10.1039/d0nj05069e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization andin vitroantiproliferative effects of novel organotin(iv) compounds with nicotinate and isonicotinate moieties on carcinoma cells

Abstract: Novel triorganotin(iv) nicotinates and isonicotinates were successfully synthesized and fully characterized. The preliminary results for their in vitro antiproliferative activity against the mouse colon carcinoma C26 cell line are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…For five-coordinated setups the degree of distortion can be quantitatively defined by parameter τ. 12,48 The values of τ = 0.71 for Ph 3 SnL1a and τ = 0.84 for Ph 3 SnL2 correspond to the distorted trigonal-bipyramidal geometry. 49,50 The sum of the The correlation between experimentally and theoretically determined geometric parameters was evaluated using two statistical parameters: the correlation coefficient (R) and the mean absolute error (MAE).…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…For five-coordinated setups the degree of distortion can be quantitatively defined by parameter τ. 12,48 The values of τ = 0.71 for Ph 3 SnL1a and τ = 0.84 for Ph 3 SnL2 correspond to the distorted trigonal-bipyramidal geometry. 49,50 The sum of the The correlation between experimentally and theoretically determined geometric parameters was evaluated using two statistical parameters: the correlation coefficient (R) and the mean absolute error (MAE).…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…Considering these aspects, many triorganotin(IV) derivatives with various oxygen‐donor ligands, that is, carboxylic acids (e.g., 4‐methoxyphenylacetic, [ 27 ] trifluoroacetic, [ 28 ] 3,5‐di‐ tert ‐butyl‐4‐hydroxybenzoic, [ 29 ] and nicotinic and isonicotinic acid [ 30,31 ] ), amino‐acids (e.g., 3‐aminobenzoic, [ 32 ] 4‐aminobenzoic, [ 32 ] or 5‐amino‐2‐chlorobenzoic [ 33,34 ] ), or nonsteroidal anti‐inflammatory drugs (NSAIDs) (e.g., indomethacin [ 35 ] and ibuprofen [ 36 ] ) displayed higher cytotoxicity with lower IC 50 values than cisplatin or other standard treatments. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…C , O ‐Chelating ligands were successfully implemented in organotin(IV) chemistry and not only, as an updated and more versatile version of the well‐known C , N ‐chelating ligand, bearing the [2‐(Me 2 CH 2 )C 6 H 4 ] moiety. [ 37 ] Therefore, a series of organometallic compounds with various p‐block metals or elements (Sn, [ 31,38 ] Se, [ 39 ] Te [ 40 ] ) were prepared starting from the readily available 2‐[(O═CH)C 6 H 4 ]Br ligand in its protected form 2‐[(CH 2 O) 2 CH]C 6 H 4 Br. Tris(2‐formylphenyl)‐stibine and ‐bismuthine were also obtained following alternative synthetic protocols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Meanwhile, some organotin carboxylates also have shown high biological activities in terms of their antitumor, antibacterial, antileishmanial and antifungal efficacies. [8][9][10][11] For example, reported by Sirajuddin et al, diphenylstannanediyl bis 2-(4-methoxy-2-nitrophenylcarbamoyl)benzoate showed significant in vitro anticancer activity for H-157 cell lines and antileishmanial activity. 12 In another example, reported by Dahmani et al, di-n-butyltin oxide bipyrazoledicarboxylate macrocyclic complexes showed high antifungal activity for Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%